Efek Aglomerasi di Indonesia: Komparasi Jawa dan luar Jawa (Jurnal Kebijakan Ekonomi, 2022)
Population density and average city’s wages in Java are higher than outside Java. The literature shows that population density can increase the productivity of firms and workers, thereby increasing the level of wages in cities. In urban economics, agglomeration economies are defined as the benefits that come when firms and people locate near one another together in cities and industrial clusters. This study estimates the agglomeration effect in Java and outside Java cities by analyzing the relationship between population density and urban characteristics with wage levels. Previous studies have shown that population density is positively correlated to wage levels at the city level. However, wage analysis at the city level has the potential to be biased because instead of reflecting the agglomeration effect, the high level of wages in cities may be due to the large proportion of highly skilled workers. This study analyzes wages at the micro-level by including individual characteristics documented in the 2019 National Labor Force Survey to overcome the bias problem. The estimation method used in this study is Ordinary Least Square (OLS) with empirical specifications adopting the model of Combes et al. (2010), and the Two-Stage Least Square (2SLS) estimation method is used with population density data in the past as an instrumental variable to overcome the endogeneity problem. This study found that population density is positively correlated with the city's wage level. However, the correlation is reduced by almost half when individual characteristics are included in the model, proving that the proportion of highly skilled workers strongly influences the high level of wages in the city.